Adzuki bean (Vigna angularis): Chemical compositions, physicochemical properties, health benefits, and food applications - Li, Hang; Zou, Liang; Li, Xin‐Yan; Wu, Ding‐Tao; Liu, Hong‐Yan; Li, Hua‐Bin; Gan, Ren‐You (Comprehensive reviews in food science and food safety, 2022)
Adzuki bean (Vigna angularis), also called red bean, is a legume of Fabaceae (Leguminosae) family. This crop is native to East Asia and is also commercially available in other parts of the world. It is becoming a research focus owing to its distinct nutritional properties (e.g., abundant in polyphenols). The diverse health benefits and multiple utilization of this pulse are associated with its unique composition. However, there is a paucity of reviews focusing on the nutritional properties and potent applications of adzuki beans. This review summarizes the chemical compositions, physicochemical properties, health benefits, processing, and applications of adzuki beans. Suggestions on how to better utilize the adzuki bean are also provided to facilitate its development as a functional grain. Adzuki bean and its components can be further developed into value‐added and nutritionally enhanced products.